2022
DOI: 10.56294/saludcyt2022194
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Data and Document Clustering pertaining to various Distance Measures

Abstract: Data is being generated at an increasing rate in a variety of fields as science and technology advance. The generated data are being saved for future decision-making. Data mining is the process of extracting patterns and useful information from massive amounts of data. The distance measure, which is used to calculate how different two objects are from one another, is one such instrument. We have conducted a comprehensive survey of how the distance measures behave when employed with different algorithms. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Additionally, Saltz and Shamshurin (2017) 62 reported that pair programming effectively improves communication and produces higher-quality code in less time for data scientists. 66 These findings suggest that this programming may be a valuable strategy to improve student learning and performance in programming. A study by Isong et al (2016) 23 examined this technique in depth.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, Saltz and Shamshurin (2017) 62 reported that pair programming effectively improves communication and produces higher-quality code in less time for data scientists. 66 These findings suggest that this programming may be a valuable strategy to improve student learning and performance in programming. A study by Isong et al (2016) 23 examined this technique in depth.…”
Section: Discussionmentioning
confidence: 95%
“…Además, el artículo aborda cómo las redes sociales rurales pueden ser utilizadas estratégicamente para potenciar la innovación y el emprendimiento, elementos clave para el desarrollo económico rural (Alonso Galbán & Izquierdo Pamias, 2022;Gómez Miranda, 2023;Torres Barreto, 2023). A través de la promoción de la economía local, la valorización de productos y servicios rurales, así como el fomento de redes de apoyo entre emprendedores, las plataformas digitales se revelan como herramientas poderosas para el desarrollo económico que, a su vez, fortalece el capital social de la comunidad (Gomes Da Silva et al, 2022;Masrom et al, 2021;Sumathi & Gunaseelan, 2022;Tuominen & Haanpää, 2022;Vrontis et al, 2021).…”
Section: Introductionunclassified
“…This issue entails economic, social, and educational consequences for the stakeholders in the global education system, ranging from the psychological impact on students to the management challenges faced by government entities 4,5 . To address the problem, predicting and managing early signs of student dropout is relevant [6][7][8][9] . This will enable educational institutions to act promptly, implementing preventive and proactive measures to address the issue and reduce the dropout rate 10 .…”
Section: Introductionmentioning
confidence: 99%